2014
DOI: 10.1089/dna.2013.2089
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity Contributes to Autophagy Induction by Regulating AMP-Activated Protein Kinase

Abstract: Exposure to microgravity is supposed to affect almost all biological systems, and we speculated that microgravity is potentially involved in autophagy regulation. A clinostat was used to simulate microgravity, and HEK293 cells that stably express GFP-LC3 were used for sensitive monitoring of autophagy induction. The clinorotation of GFP-LC3 cells resulted in autophagosome formation in the cytoplasm and a change in autophagosomal marker expression. Autophagy induction was accompanied by phosphorylation of AMPK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
(48 reference statements)
2
25
0
Order By: Relevance
“…Hyun W. Ryu et al . 30 observed increased autophagy under SM. Upregulation of AKT and subsequent migration and tube formation were seen in HUVECS subjected to clinorotation 31 .…”
Section: Discussionmentioning
confidence: 89%
“…Hyun W. Ryu et al . 30 observed increased autophagy under SM. Upregulation of AKT and subsequent migration and tube formation were seen in HUVECS subjected to clinorotation 31 .…”
Section: Discussionmentioning
confidence: 89%
“…Some papers in the literature reported that, in other cellular systems, microgravity is involved in autophagy induction [1820] and, as previously stated, cytoskeleton plays important roles in autophagy regulation [22]. In particular, in mammals, microtubules appear to be involved in the fusion of autophagosome with late endosome and to bind and transport autophagosomes, once terminally completed.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that microgravity exposure could strongly influence cytoskeleton organization [1017] and it is commonly accepted that cellular tensegrity alteration in microgravity exposed cells could explain, at least in part, the conversion of a mechanical cue into a biological response. In this regard, recent studies have revealed the importance of cytoskeletal integrity, such as F-actin and microtubules, in the physiological specific aspects of autophagy, and some papers described the capability of microgravity to induce autophagy in living cells [1822]. Autophagy is an important housekeeping physiological process that is involved in cellular remodeling during development, elimination of aberrant organelles, or misfolded proteins and in the recycling of unnecessary cellular components to compensate for the limitation of nutrients during starvation.…”
Section: Introductionmentioning
confidence: 99%
“…Because muscle cell death and atrophy is related to accelerated autophagic flux, autophagic flux inhibitors like conessine can be useful to prevent muscle cell death. Recently, we also reported that microgravity in space can potentially affect muscle weakening by regulating autophagy, and an autophagic flux inhibitor like conessine would be potentially useful in such a setting [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy (specifically, macroautophagy), a catabolic pathway responsible for degrading protein aggregates and organelles [ 1 ], can be induced by extracellular stress (e.g., nutrient starvation, hypoxia, high temperature, and microgravity) [ 2 , 3 ]. The dynamic process of autophagy, including the conversion of autophagosomes into autolysosomes, is termed autophagic flux, and both the activation and inhibition of autophagic flux result in an increase of autophagosomes in the cytoplasm [ 4 ].…”
Section: Introductionmentioning
confidence: 99%